GAYA KOMUNIKASI DALAM BINGKAI KEPEMIMPINAN BAGI FIGUR PEREMPUAN - Indriani, Sri Seti; Prasanti, Dhita (Jurnal Nomosleca, 2018)
Good leadership requires competence in communicating with members, how to communicate the leadership of an organization or institution to achieve its goals. In this modern society, more and more women become leaders in their organization which in some parts of society in Indonesia, It is still rare to find women responsible. This study aims to find out more about responsible women in an institution / organization that focuses on how they communicate with their members to achieve goals, so that the title that emerges in this research is "Communication Style in the Frame of Leadership for Women". The focus of this research is to know the style of leadership communication on the female figure. The research used qualitative approach with case study method. Data collection techniques used were in-depth interviews, documentation studies and observation. The fourth informants were chosen by purposive sampling technique. The results showed that leadership style of communication in this female figure include informative style; directing; confirm; participate; granting delegations; remind; and evaluation. Keywords: Communication Style, Leadership, Women, Institute of Language StudiesDOI : https://doi.org/10.26905/nomosleca.v4i1.1987